La charpente de la nef de la cathédrale de Bourges - Frédéric Epaud (Revue Archéologique du Centre de la France)
The Gothic cathedral of Bourges was built in two phases, with the chancel from 1195 to 1214 then the nave from 1225 to 1255, after a 10-year interruption to the building work. The original roof structure was in part reconstructed on all the sides, following a fire in 1559, and on the middle part of the great nave, between 1747 and 1754, due to the removal of the false transept and its spire. The archaeological survey of the structure remaining on the Gothic nave, and the dendrochronological analysis of its timber shows that the trees were felled over a period from 1230 to 1257, with two major felling campaigns between 1240 and 1244 and autumn-winter 1254-1255, just prior to the implementation and lifting of the structure in 1256 or soon after. These successive fellings suggest a supply to the site from donations of wood or forest plots used immediately, requiring the storage of wood pending construction. The trussed rafter structure was built according to a first plan that was modified while construction was underway to insert a longitudinal bracing device, with a new structure of main trusses to support it. This axial bracing was doubled by a second situated in the plane of the rafters, with a date, proven by dendrochronology for the first time, in the middle of the thirteenth century. In 1262 the eastern bays of the structure of the nave were changed to enable the addition of a wooden spire and a false transept directly below the fourth arch span.